The Authorities of Owner’s on the Detached Parts in the Ownership of the Floors and Apartments : A Comparative Study - Shaker , Zeena; Ibrahim, Ali (Journal of Legal Sciences, 2023)
The right of the owner of the floor or apartment over his detached unit is a full ownership right, which simplifies to its owner the powers of use, exploitation and disposal, provided that the owner’s powers in the system of ownership of floors and apartments, as well as their adherence to the general restrictions of ownership, remain also restricted by agreement restrictions, the source of which is title deeds And the building bylaws, which are drawn up by the Building Owners Association.